유산균을 첨가한 아로니아 발효액의 생리활성 평가 - 선유경(Yoo Kyung Seon); 성혜미(Heami Sung); 박정진(Jeongjin Park); 전우진(Woojin Jun) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2024)
본 연구에서는 아로니아에 올리고당과 배즙을 첨가하여 유산균으로 24시간 발효한 아로니아 발효액의 발효 전후 생리활성을 측정하였다. 대사증후군 관련 생리활성인 항산화, 항고혈압, 항콜레스테롤 및 항당뇨를 측정하기 위해 DPPH 라디칼 소거능, ACE 저해 활성, HMG-CoA 환원효소 억제 활성 및 α-glucosidase 저해 활성을 측정하였다. 항산화 활성은 24시간 발효군이 0시간 발효군보다 14.03% 유의적으로 증가했으며, 항고혈압 활성은 0시간 발효군보다 24시간 발효군에서 약 9.00% 더 높은 활성을 나타내었다. 항당뇨 활성은 24시간 발효군에서 0시간 발효군보다 13.63% 유의적으로 증가하였다. 항비만 활성을 평가하기 위해 3T3-L1 세포에서 Oil Red O 염색법을 이용한 지방축적 저해 정도 및 세포 내 중성지방 함량을 측정한 결과, 24시간 발효군에서 지방축적 저해 및 중성지방의 함량이 감소하는 것을 확인하였다. 이상의 결과로부터 24시간 발효군은 0시간 발효군보다 생리활성에 효과적인 결과를 보여주었고, 대사증후군에 도움을 주는 아로니아를 활용한 기능성 음료와 같은 가공식품으로 활용할 수 있는 잠재적 가능성을 보여주었다. This study examined the physiological activities (antioxidant, anti-hypertensive, anti-cholesterol, anti-diabetic, and anti-obesity) of Aronia fermented with oligosaccharides and pear juices. The Aronia, oligosaccharides and pear juices were fermented with lactic acid bacteria for 24 h, and its activity before and after fermentation was measured. The DPPH radical scavenging activity in the Aronia fermentation extracts was increased by fermentation. Anti-hypertensive and anti-diabetic activities were significantly higher after 24 h of fermentation than in the control. No anti-cholesterol activity was observed after fermentation. Furthermore, the Aronia fermentation extract had significant inhibitory activity on adipocytes differentiation in the 3T3-L1 preadipocytes as assessed by measuring fat accumulation using Oil Red O staining. The intracellular triglyceride levels were also reduced by 8.7% at the same concentration. The level of free glycerol released into the culture medium decreased by 27.1% after treatment with the Aronia 24 h-fermented product. These results suggest that Aronia fermentation with lactic acid bacteria improves diverse physiological activities and can be developed as a functional material or food. KCI Citation Count: 0